Menjelajahi Dinamika Pangan di Era Perubahan Iklim Terhadap Dampak di Indonesia dan Proyeksi Masa Depan: A Systematic Review - Hakim, Dwi Ratnawaty; Rahmiwati, Anita; Flora, Rostika; Novrikasari (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Indonesia is heavily dependent on the agricultural industry, which is one of the primary pillars of the country's economy, hence food security is very crucial. Since the majority of people work in agriculture, ensuring there is a sufficient supply of food is essential to preserving social and economic stability. Furthermore, Indonesia's geographical and cultural diversity poses particular difficulties in addressing the various dietary requirements of its many areas. In light of climate change, natural disasters, and other global issues that may have an impact on food supply, food security is also a strategic consideration. The project aims to (1) assess the degree of susceptibility of Indonesia's food system to climate change and (2) develop solutions for adaptation and mitigation that may be put into practice to enhance food security in the face of these consequences. This study provides an organized overview of food dynamics in the context of climate change and how it affects Indonesia. The literature from prestigious national and international journal articles is one of the research data sources. The findings demonstrate how difficult it is to comprehend how climate change is affecting Indonesia's food supply, which emphasizes how complicated the problems are. Farmers have put adaptation plans into place, but resource access and climate unpredictability still present obstacles. Climate change has an impact on the national economy and export-related activities. Therefore, to attain both economic stability and food security, comprehensive support and integrated policies are required. To meet the difficulties of climate change in the agricultural sector, farmers' adaptation methods, cross-sectoral cooperation, and access to climate information are essential.